Strategi Epistimologis Implementasi Pendidikan Holistik Pada Pondok Pesantren - Muhammad Nasrudin; Hilman Harun; Ahmad Salim; Ahmad Dimyati (Universitas Cokroaminoto Yogyakarta, 2021)
the basic principles of Islamic boarding school education, namely; Al Muhafadhah ala al-qadim al shalih wa al akhdzu bi al jadid al ashlah. This principle has encouraged pesantren to maintain good old Islamic values without denying better changes. This paper intends to explore two sides of the coin for Pondok Persantren where one side is a distinct advantage for but can be a boomerang that hinders the progress of Islamic education based on understanding the basic elements and values of Islamic boarding schools and, then contributing thoughts in building a holistic Islamic boarding school education so that can follow the development of science without losing the obligation to maintain basic values. Holistic pesantren education can only be achieved if it is reaffirmed that the elements of the boarding school education system are not oriented towards learning religious knowledge but how kyai, teachers / ustaz and santri can learn to live in religion.